Infrared Laser Application to Wood Cutting - Aniszewska, Monika (Materials (Basel), 2020)
While lasers are widely used across various industries, including woodworking, few studies to date have addressed the issue of cutting fresh wood. In the present investigation, wood stemming from fresh tree branches was cut at different laser powers and beam travel speeds. A fiber laser and a CO(2) laser were used for the research. The cellular structures of the cut surfaces were examined, with some of them found to be covered with a layer of compacted, charred cells. This may be a favorable phenomenon, preventing the invasion of pathogens via the wounds caused by laser beam branch cutting in nurseries, plantations, and orchards.